Educational Values ​​in the Qur'an Surah al-Jum'uah (Study of Tafsir Al-Misbah and Al-Wasith) - Nurvia Agnes Monika; Robin Sirait (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2025)
Artikel ini mengkaji nilai-nilai pendidikan yang terkandung dalam Surah Al-Jum’uah berdasarkan dua tafsir terkemuka, yaitu Al-Misbah karya Quraish Shihab dan Al-Wasith karya Wahbah Zuhaili. Penelitian ini bertujuan untuk menggali dimensi pendidikan yang dapat dijadikan panduan dalam kehidupan sehari-hari. Surah Al-Jum’uah memiliki pesan moral dan spiritual yang mendalam, terutama terkait dengan pentingnya ilmu, pemanfaatan waktu, dan keutamaan ibadah. Dalam Tafsir Al-Misbah, Quraish Shihab menyoroti pesan-pesan universal Al-Qur’an yang relevan dengan tantangan modern, sementara Tafsir Al-Wasith oleh Wahbah Zuhaili memberikan pendekatan linguistik dan analisis tematik yang memperkaya pemahaman tentang nilai-nilai pendidikan yang terkandung dalam surah ini. Metode penelitian yang digunakan adalah kajian pustaka dengan pendekatan analisis tematik, yang mencakup identifikasi tema-tema utama, interpretasi teks berdasarkan kedua tafsir, dan penarikan kesimpulan dari temuan-temuan tersebut. Hasil penelitian menunjukkan bahwa nilai-nilai pendidikan dalam Surah Al-Jum’uah meliputi nilai keimanan, yang mengajarkan kesadaran tentang kebesaran Allah dan pentingnya pengakuan atas tauhid; nilai ilmu pengetahuan, yang menekankan pentingnya pendidikan holistik mencakup aspek spiritual dan intelektual; serta nilai amal shaleh, yang menegaskan perlunya keseimbangan antara ibadah dan aktivitas duniawi. Artikel ini diharapkan dapat memberikan kontribusi bagi kajian pendidikan Islam serta menjadi pedoman praktis bagi umat Islam dalam menjalani kehidupan yang berlandaskan nilai-nilai Al-Qur’an.Kata Kunci: Nilai-nilai Pendidikan; Tafsir Al-Misbah dan Al-Wasith; Pendidikan Islam; Surah Al-Jum’uah This article examine the educational values contained in Surah al-Jum'uah based on two prominent interpretations, namely Al-Misbah by Quraish Shihab and Al-Wasith by Wahbah Zuhaili. The objective of this study is to explore the educational values contained in Surah al-Jum'uah that can serve as a guide in everyday life. Surah al-Jum'uah contains a profound moral and spiritual message, particularly concerning the significance of knowledge, the utilization of time, and the merits of worship. In the interpretation of al-Misbah, Quraish Shihab emphasizes universal messages of the Qur'an that are pertinent to contemporary challenges. Conversely, Al-Wasith's interpretation by Wahbah Zuhaili employs a linguistic approach and thematic analysis to enhance the comprehension of the educational values contained in this Surah. The research method employed is a literature study with a thematic analysis approach, which includes the identification of the main themes, the interpretation of text based on the two interpretations, and the drawing of conclusions from these findings. The results of the study indicated that the educational values inherent in Surah al-Jum'uah encompass the value of faith, which fosters awareness of the grandeur of God and the significance of recognizing monotheism; the value of science, which underscores the importance of holistic education encompassing spiritual and intellectual dimensions; and the value of charity pious, which substantiates the necessity for a balance between worship and worldly endeavors. This article is expected to contribute to the study of Islamic education and become a practical guide for Muslims in living a life based on the values of the Qur'an.Keywords: Education Values; Tafsir Al-Misbah and Al Wasith; Islamic Education; Surah Al-Jum’uah